Deciphering the molecular function of the α7 nicotinic receptor for its implementation as a clinical drug target - Bouzat, Cecilia Beatriz (2024)
The α7 nicotinic receptor is a pentameric ligand-gated ion channel widely expressed in the central nervous system, where it plays key roles in cognition, attention, and memory. It is also found in non-neuronal cells, contributing to anti- inflammatory and neuroprotective processes. The enhancement of α7 activity is emerging as a promising therapeutic strategy for neurodegenerative disorders, such as Alzheimer’s and Parkinson’s diseases, as well as neurological and inflammatory conditions. Despite promising preclinical and clinical data, no α7- specific ligand has been approved for clinical use yet. Our objective is to elucidate the molecular function of α7 and its modulation under physiological and pathological conditions, in order to advance its potential as a therapeutic target. We expressed α7 in mammalian cells and assessed its function using single- channel and macroscopic current patch-clamp recordings. Through this approach, we identified natural and synthetic compounds that act as novel α7 positive allosteric modulators, exhibiting neuroprotective properties and offering new molecules with therapeutic potential. Additionally, we characterized new mechanisms of α7 modulation, including interactions with oligomeric amyloid beta peptides associated with Alzheimer's disease, cannabidiol, phosphorylation, calcium, and other nicotinic receptor subunits. These findings provide critical insights to be considered in future clinical trials. By investigating α7 function from a molecular perspective, our results lay the groundwork for its implementation as a viable therapeutic drug target.